2016
DOI: 10.1038/mi.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 sustains the survival of Foxp3+ regulatory cells during late phase of oropharyngeal candidiasis infection

Abstract: As CD4+CD25+Foxp3+ regulatory T cells (Tregs) play crucial immunomodulatory roles during infections, one key question is how these cells are controlled during antimicrobial immune responses. Mechanisms controlling their homeostasis are central to ensure efficient protection against pathogens, as well as to control infection-associated immunopathology. Here we studied how their viability is regulated in the context of mouse oropharyngeal candidiasis (OPC) infection, and found that these cells show increased pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…TGF-β inactivation had a largely direct effect on Tregs, with decreased tumor infiltration and increased apoptosis, in line with its known properties (34,37,47). In contrast, the effect of VEGF on Treg appears more indirect.…”
Section: Discussionmentioning
confidence: 57%
“…TGF-β inactivation had a largely direct effect on Tregs, with decreased tumor infiltration and increased apoptosis, in line with its known properties (34,37,47). In contrast, the effect of VEGF on Treg appears more indirect.…”
Section: Discussionmentioning
confidence: 57%
“…To test this hypothesis, we treated the cells with heat killed Candida albicans germ tube (HKGT) (10 7 /ml), α-CD3 (1 μg/ml, α-CD28 (2 μg/ml), and TGF-β1 (5 ng/ml), to examine the frequency of Foxp3 + cells after 5 days. We employed this in vitro cell culture system because: 1) We have previously found that HKGT can cause in vitro proliferation of T regs in TLR-2 dependent manner; 2) TGF-β1 is important for survival of Foxp3 + T regs during oral CA infection as well resistance to Candida in vivo ( 2 , 32 , 33 ); and 3) Activating T cells in a whole tissue culture system including the local antigen presenting cells (APC) is more physiological than using purified T cell cultures because APC secrete appropriate cytokines in the milieu ( 2 , 32 ). As expected, HKGT stimulation increased the proportion of Foxp3 + cells among CD4 + T cells in FYcre cultures compared to those found ex vivo ( Figures 1A, C , upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that increased proportions of T regs may also be attributed to preferential apoptosis or pyroptosis of conventional CD4 + T cells, including Th17 cells in the mucosa. We have previously shown that conventional CD4 T effector cells are highly susceptible to FAS-mediated apoptosis compared to T regs in vitro and in vivo ( 145 ). In our future studies, we will examine whether differential sensitivities of Th17 cells and T reg cells to FAS mediated apoptosis and, or pyroptosis, also contribute to increased T reg /Th17 ratio in mucosa during HIV infection.…”
Section: T Reg Changes In Mucosamentioning
confidence: 99%